Topical application of the plant extract SDTL-E in ovariectomized rats: A potential new approach for treating osteoporosis - Shih, Hui-Yuan; Lu, Jun-Hua; Xiong, Ai-Hua; Tse, Juliana Man-Wai; Wong, Ben Siu-Tak (Frontiers in Medicine, 2022)
Current osteoporosis medications have drawbacks of causing side effects and having slow onset, therefore developing osteoporosis drugs with faster onset and less side effects is essential. This study investigated the effects of the natural plant extract, SDTL-E, in ovariectomized (OVX)-induced osteoporosis rats. Rats were randomly assigned to sham operation control group (Control Group); OVX rat model group (Model Group) or OVX rat SDTL-E treatment group (SDTL-E Group). All groups underwent ovariectomy, but the Control Group did not have the ovaries removed. SDTL-E Group was treated with SDTL-E, Model and Control Groups were treated with vegetable oil, treatments were topically applied twice daily for 20 days. Results showed when compared with Model Group, SDTL-E Group significantly restored serum estradiol back to near Control Group level, serum ALP activity, serum and urinary calcium were significantly decreased, bone mechanics indicators increased and trabecular bone numbers slightly increased. These results demonstrated 20 days of SDTL-E topical treatment improved bone strength and trabecular bone structure in OVX-induced osteoporosis rats. The underlying mechanisms include restoring estradiol level, reducing bone turnover, net bone resorption, bone calcium loss and calcium excretion through kidney. These findings suggest topical application of plant extract is a potential new approach with quick efficacy for treating osteoporosis.